Deep Neural Model for Duplicate Question Detection Using Support Vector Machines (Svm) - Naresh Kumar, Sanjay Kumar, Seema Rani, Avadhesh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Stack Overflow has been a core component of the toolset of the developer. This rise in influence was followed by a Stack Overflow group initiative to preserve the Content consistency. One of the threats that threaten the persistent growth of duplicated questions is consistency. Resolution of Prior research on the automated identification of this problem Questions multiplied. DupPredictorand Dupe are two essential solutions. We carried out aDupPredictor and Dupe’s observational replica analysis. While the findings are important, both works are not freely accessible, so hindering their introduction. The following work depends on them in the science literature. Wecarried out a DupPredictor observational replica analysis And Dupe. Our findings are not stable in various ways,sets of methods and data sets. To illustrate the replication barriersfor these methods and approaches are high. In addition, if more is necessary we observe a decrease in efficiency of our two recentlyRecall-rate reproductions over time, as the numberof questions is increased. The following are our resultsof study on the identification of questions duplicating inquiry to claim and Respond Communities with their assumptions. The findings of this paper are systemic and comparative tests with main technique stylesfor predictive question identification duplication detectionApplied to increasingly broad data collections, such thatto research the profiles of learning of this mission, approaches and assesses the merits. This research has been carried out by using the latest publication for research purposes, Probable a new engine by Quora online reply query dataset with more than 100000 marked pairs Duplicate portions of questioning are components.